Psychometric evaluation of two indices assessing stigma toward opioid misuse and treatment among health care providers. (4th March 2022) - Brown, Robyn Lewis; Batty, Evan; Lofwall, Michelle; Kiviniemi, Marc; Kizewski, Amber
ABSTRACT: Background : Stigma is described as highly relevant to the treatment context for opioid use disorder (OUD) partly because it is known to influence clinicians' treatment decisions and care provision. However, appropriate measures are needed to test the salience of stigmatizing views held by clinicians directly. Objective : This study assessed dimensionality, reliability, and validity evidence for two measures – of public stigma toward opioid misuse and clinician stigma associated with medication for opioid use disorder (MOUD), respectively. Methods : Psychometric tests were conducted based on survey data collected from a sample of 144 clinicians participating in a buprenorphine waiver training program (30% female). Results : Factor analysis indicated that the indices of stigma associated with opioid misuse and MOUD stigma are best represented as separate measures. Spearman-Brown Prophesy estimates (opioid misuse stigma = .88; MOUD stigma = .93) and Cronbach's alpha coefficients (opioid misuse stigma = .93; MOUD stigma = .91) supported the reliability of both measures. Construct validity evidence was additionally found in correlation tests based on provider background characteristics, and discriminant validity evidence is supported by the between-factor correlation coefficient (r = .44, p = .04) for the opioid misuse stigma and MOUD stigma indices. Conclusions : Both indices examined in this report are psychometrically acceptable measures for assessing general bias among health care providers toward persons who misuse opioids and toward those seeking MOUD treatment. Further consideration of these forms of bias are recommended in future research to improve clinical practice and increase the implementation of MOUD treatment.